Front Cover Image. Issue 2 (16th January 2023) - Yang, Zhao‐Kai; Qu, Cheng; Pan, Shi‐Xiang; Liu, Yan; Shi, Zhuo; Luo, Chen; Qin, Yao‐Guo; Yang, Xin‐Ling
Abstract : The cover image is based on the Research Article Aphid‐repellent, ladybug‐attraction activities, and binding mechanism of methyl salicylate derivatives containing geraniol moiety by Zhao‐Kai Yang et al., https://doi.org/10.1002/ps.7245 . Abstract : The cover image is based on the Research Article Aphid‐repellent, ladybug‐attraction activities, and binding mechanism of methyl salicylate derivatives containing geraniol moiety by Zhao‐Kai Yang et al., https://doi.org/10.1002/ps.7245 .